The Discourse in Lontaraq Meongpalo Karellae: An Anthropological Perspective - Slippy, Janeke Peggy; Karim, Abd; Nur, Muhammad; Hamid, Wardiah; Hamsiati, Hamsiati; Saputra, Muhammad Ali (Universitas Andalas, 2024)
This article discusses the Lontaraq Meongpalo Karellae manuscript from an anthropological perspective. The manuscript narrates the story of a cat subjected to violence by humans, leading to the descent of celestial beings known as Dewata Sangiangseri to administer 'retribution' against those who mistreat animals. The manuscript also explores the relationships between humans, nature, and other living beings to foster harmonious coexistence for environmental preservation. This narrative imparts ethical lessons from an anthropological and cultural standpoint.The study employs an anthropological approach to analyze cultural practices among the Bugis community, particularly in maintaining harmony among humans, nature, and the surrounding environment. Through the Maddoja Bine ritual, these practices substantiate how the Lontaraq Meongpalo Karellae manuscript provides concrete implications for Bugis ethnic entities to nurture and care for the environment. Furthermore, this research enables a deeper understanding of the dynamics of traditional Bugis society, especially in the contexts of social interaction, family structure, and inherited cultural values. Oral traditions, myths, and rituals constitute integral aspects of the cultural identity of the community, effectively manifesting as relational entities within historical and environmental contexts, thereby underscoring their relevance in contemporary anthropological studies.